Content Analysis of Thinking and Lifestyle Text Books of The First Secondary Schools in regard to Self- care - Ali Imanzadeh; Shahram Vahedi; Fatemeh Gharaghani (علوم تربیتی از دیدگاه اسلام)
The purpose of the research content analysis of the fist secondary school text books( thinking and lifestyle) in regard to self- care. The current research is a quantitative content analysis.  In this research, the research community, the content of the thinking and lifestyle textbooks of the first secondary school (7th, 8th) academic year of 1402-1401 were selected.  The statistical sample of the research included the seventh and eighth grade thinking and lifestyle textbooks (common for boys and girls) and the method of sampling was also targeted.  Content analysis techniques (checklist) were used to collect information.  The initial form of this checklist is prepared from the literature and theoretical foundations of the research.  In order to check the validity of its content, the prepared checklist was given to the tutors and advisors as well as five experts in this field for modification and after applying their opinions, the content analysis checklist was finalized.  The unit of analysis and review in this research was all the components of the book "Thinking and Lifestyle" of the first secondary school (content, pictures, activities, questions) and the unit of registration was a theme.  In this research, the Shannon entropy method was used to analyze the data.  In this order, the data were normalized and the importance coefficient, information load and standard deviation of each component were calculated.  The findings of the research showed that the seventh and eighth grade thinking and lifestyle books paid little attention to self-care.  Among the studied components, the most frequency is related to the physical component (observing proper clothing and according to the seasons), emotional (being kind to yourself and others), psychological (feeling of sufficient self-confidence).  The lowest frequency is related to the components of spiritual self-care, and most of their sub-components (such as reciting and listening to the verses of the Qur'an and participating in religious ceremonies and rituals, doing good deeds, helping the needy, giving thanks for God's blessings) have not been paid attention to.  Self-care skills can be realized by including the components of self-care in educational books and taking a balanced look at it in books of the first secondary school, especially books on thinking and lifestyle.